4(3x+2)+1=-15

Simple and best practice solution for 4(3x+2)+1=-15 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(3x+2)+1=-15 equation:


Simplifying
4(3x + 2) + 1 = -15

Reorder the terms:
4(2 + 3x) + 1 = -15
(2 * 4 + 3x * 4) + 1 = -15
(8 + 12x) + 1 = -15

Reorder the terms:
8 + 1 + 12x = -15

Combine like terms: 8 + 1 = 9
9 + 12x = -15

Solving
9 + 12x = -15

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9' to each side of the equation.
9 + -9 + 12x = -15 + -9

Combine like terms: 9 + -9 = 0
0 + 12x = -15 + -9
12x = -15 + -9

Combine like terms: -15 + -9 = -24
12x = -24

Divide each side by '12'.
x = -2

Simplifying
x = -2

See similar equations:

| 2x^2=30x-100 | | -40+-55-10=-12v+36 | | 15-7=8 | | 9=n+7 | | P+x=8+f+(-f) | | -2x-4y=2x-4 | | -8=-2x-6 | | -98+x=56-10x | | -17-37=26 | | 15-7=x | | 2x-14=x-7 | | 6y+5x=-3 | | -2x+5x^2-7=0 | | -4=t+8 | | -5+33=7 | | -7r-8=14 | | -5+48=7 | | 3(y-9)4=-2y | | 4z-43=2z+80 | | 4(2z-8)-(z-9)=8(8-7z) | | -5+36=7 | | -5g+1.2=-18.8 | | 10x-186=90-2x | | 7(k+9)=9(k-5)-14 | | 3y=4(x+6) | | -(5x+8)+12=17+17 | | 4f+2= | | -7j+62=-2g+12 | | 11b^2-71b-42=0 | | 5-c-10-5c-2=8 | | M=-4m+15 | | -4x-6x=20 |

Equations solver categories